PENGARUH PELAKSANAAN PROGRAM ASRAMA TERHADAP KEMANDIRIAN MAHASISWA ASRAMA IAKN TARUTUNG - Chelshe Hutabarat; Betty Pakpahan; Abai Tambunan; Lasmaria Lumbantobing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the dormitory program on the independence of IAKN Tarutung students in the 2025/2026 academic year. The research method used in this study is an inferential quantitative research method. The population in this study were all IAKN Tarutung dormitory students in the 2025/2026 academic year, totaling 191 people. In this study, the number of samples was set at 147 people using the Slovin formula, while the sampling technique used was stratified random sampling. Data were collected with a closed questionnaire of 30 items. The results of the data analysis showed that there was an effect of the implementation of the dormitory program on the independence of IAKN Tarutung dormitory students in the 2025/2026 academic year. Proven through the following data analysis: 1) Analysis Requirements Test: a) The results of the correlation coefficient test obtained a value of rxy = 0.897 > 0.161, thus it is known that there is a positive relationship between variable X and variable Y. b) The coefficient significance test obtained a value of tcount = 24.429 > ttable 1.655, thus there is a significant relationship between variable X and variable Y. 2) Influence test: a)